Pengaruh Pemberian Yogurt Kersen (Muntingia calabura L.) Terhadap Penderita Asam Urat di Kota Palopo - Ervianingsih Ervianingsih; Chitra Astari; Audina Prastiwi; Rosvani Kalope (Jurnal Kesehatan Komunitas, 2022)
Treatment of hyperuricemia is a chronic and lifelong treatment, one of the steps taken in dealing with disease and hyperuricemia is using medicinal plants, one of which is cherry fruit. Therefore, it is made in the form of a health drink in the form of cherry yogurt. The purpose of this study was to determine the effect of giving cherry yogurt on reducing uric acid levels in hyperuricemic patients. The research design used in the study was a quasi-experimental design with a pre-post test group design. This research was conducted by examining blood glucose levels after administration of Cherry yogurt (Muntingia calabura L) Treatment. Starting with the pre-test and after giving the treatment (Treatment) a re-measurement (post test) was carried out in patients suffering from gout. The sampling technique is purposive sampling with a total sample of 18 people. The results of the analysis showed that there were differences in uric acid and blood sugar levels in the group receiving the cherry yogurt treatment, which was an average of 7.7 mg/dl after being given cherry yogurt therapy to an average of 6.9 mg/dl with an average difference of 6.9 mg/dl. an average of 0.8 mg/dl. While the control group that was not given treatment (Treatment) was an average of 7.87 mg/dl after treatment to an average of 7.79 mg/dl with an average difference of 0.07 mg/dl. The suggestion from the research conducted is that it is necessary to make a finished product of health drink from yohurt kersen so that patients can get the product easily.